PENGARUH MODEL PEMBELAJARAN KOOPERATIF TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN EDUCAPLAY TERHADAP HASIL BELAJAR KOGNITIF SISWA SEKOLAH DASAR - Ratih Fatimah; Afridha Laily Alindra; Wina Mustikaati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Improving learning outcomes is important to measure student progress during the learning process. This study was motivated by the low learning outcomes of elementary school students. This study aims to determine whether the Teams Games Tournament (TGT) cooperative learning model assisted by Educaplay can improve students' cognitive learning outcomes compared to the STAD cooperative learning model, as well as the effect of the TGT cooperative learning model on student learning outcomes. A total of 60 research participants participated in the quasi-experimental research using a non-equivalent pretest posttest control group design. Documentation and learning outcomes assessment were used as research instruments. Data analysis showed that the experimental class using the Teams Games Tournament (TGT) cooperative learning model assisted by Educaplay experienced an N-Gain increase of 63%, compared to 50% for the control class using the STAD cooperative learning model. The results showed that students who received teaching using the Teams Games Tournament (TGT) type cooperative learning model assisted by Educaplay had better science learning outcomes compared to students who used the STAD type cooperative learning model, and the Teams Games Tournament (TGT) type cooperative learning model assisted by Educaplay had a positive effect on student learning outcomes by 25.1%.